FabG moonlights as an extracellular adhesin mediates cytoadhesion of Streptococcus suis via interaction with plasminogen - Genglin Guo; Yu Zhou; Pei Li; Quan Li; Yanfei Yu; Wei Zhang (BMC Microbiology)
Abstract Streptococcus suis serotype 2 (SS2) is an important zoonotic bacterial pathogen that can causes meningitis, septicemia, endocarditis, arthritis, pneumonia, and streptococcal toxic shock-like syndrome in pigs and humans. FabG, an essential reductase in the bacteria type II fatty acid synthesis pathway, is present in the extracellular space and binds to many extracellular matrix components of the host. In this study, we investigated the moonlight function of FabG. First, we found that the transcription of FabG in virulent SS2 strains was significantly higher than in avirulent strains, indicating that FabG may be involved in the pathogenesis of S. suis. After preparation of recombinant proteins, we found that the recombinant FabG could directly bind to host epithelial cells. ELISA, SPR, and Far-Western blot assays showed that rFabG could bind to the host plasminogen. Furthermore, the ability of rFabG to recruit host plasminogen to degrade the host ECM component was visualized by electron microscopy. Moreover, we found that rFabG could bind to complement C3 in serum and enhance the survival ability of S. suis in serum. Collectively, these data imply that FabG is a moonlight adhesin involved in S. suis cytoadhesion and a plasminogen receptor that could help S. suis break through the host barrier or evade immune defenses.